Lemahnya Pertanggungjawaban Korporasi Tambang terhadap Pencemaran Lingkungan: Solusi Penerapan Sanksi Hukum dan Pemulihan Ekologis - Rayi Kharisma Rajib; Ahmad Munawar Nuril Ibtisan; Euclid Abraham Pasaribu (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The mining sector in Indonesia makes a significant contribution to the national economy, but at the same time causes serious environmental impacts, including water pollution, land degradation, and the loss of biodiversity. Although Indonesia has a comprehensive legal framework through Law No. 32 of 2009 on Environmental Protection and Management (UUPPLH), its implementation in practice is still far from optimal. This study aims to analyze the factors hindering the implementation of mining corporations’ accountability for environmental pollution, as well as to assess the effectiveness of legal sanctions and ecological restoration mechanisms in enhancing corporate accountability. The research findings indicate that the weakness of mining corporations’ accountability stems from three primary factors: the lack of oversight and institutional capacity among law enforcement agencies, low corporate compliance with environmental regulations, and a significant gap between regulations and their implementation on the ground. Furthermore, the multi-tiered sanction system under the Environmental Protection and Management Law (UUPPLH) which includes administrative, civil, and criminal sanctions is normatively adequate but has failed to produce a tangible deterrent effect, as the sanctions imposed are often disproportionate to the corporations’ economic gains. Mechanisms for ecological restoration through reclamation, rehabilitation, and ecological compensation have also not been optimally implemented due to weak post-mining oversight. This study concludes that the effectiveness of environmental law is not solely determined by the comprehensiveness of regulations, but by the consistency of enforcement and the commitment of all stakeholders to ensuring ecological sustainability.